ANALISIS HUKUM PERSAINGAN USAHA TENTANG KERJA SAMA KEMITRAAN PEMBANGUNAN DAN PENGELOLAAN PERKEBUNAN KELAPA SAWIT PERSPEKTIF ISTISLAH (STUDI PUTUSAN KPPU NOMOR 02/KPPU-K/2023) - Maya Rein; Mustapa Khamal Rokan (Fakultas Hukum, Universitas Semarang, 2025)
This study aims to analyze unilateral control of partnership cooperation from the perspective of business competition law and the principle of benefit (istislah), as well as to review the competence of the authority of the KPPU decision Number 02/KPPU-K/2023 in providing protection to small businesses, namely plasma farmers. This study uses a normative legal research method with a judicial case approach, which examines laws and regulations related to business partnerships and KPPU decisions as the main material for analysis. The data used comes from legal documents, partnership agreements, laws and regulations, and KPPU decisions, which then this analysis technique is normative juridical. The results of the study show that PT Hardaya Inti Plantations was proven to have violated Article 35 paragraph (1) of Law Number 20 of 2008, because it unilaterally controlled small businesses (farmer cooperatives), did not provide transparent financial accountability reports, and set the purchase price of fresh fruit bunches not in accordance with government regulations. This has implications for financial losses for plasma farmers, who are burdened with debt without a clear payment mechanism for losses in unilateral control of large businesses that monopolize the partnership system. In terms of perspective, this practice is contrary to the principles of justice and welfare, because it harms the weaker party in the partnership. As a suggestion, it is necessary to strengthen regulations and supervision from the KPPU, including the application of stricter sanctions against large business actors who abuse partnerships. In addition, transparency in partnership agreements must be clarified through more detailed regulations, as well as legal assistance for plasma farmers so that they have a stronger bargaining position in partnership agreements. Abstrak Penelitian ini bertujuan untuk menganalisis penguasaan sepihak kerja sama kemitraan dalam perspektif hukum persaingan usaha dan prinsip kemaslahatan (istislah),serta meninjau kopetensi kewenangan putusan KPPU Nomor 02/KPPU-K/2023 dalam memberikan perlindungan kepada usaha kecil yakni petani plasma.Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan yudisial case kasus (case approach), yang mengkaji peraturan perundang-undangan terkait kemitraan usaha serta putusan KPPU sebagai bahan utama analisis. Data yang digunakan berasal dari dokumen hukum, perjanjian kemitraan, peraturan perundang-undangan, serta putusan KPPU, yang kemudian teknik analisa ini bersifat yuridis normatif.Hasil penelitian menunjukkan bahwa PT Hardaya Inti Plantations terbukti melanggar Pasal 35 ayat (1) UU Nomor 20 Tahun 2008, karena menguasai usaha kecil (koperasi tani) secara sepihak, tidak memberikan laporan pertanggungjawaban keuangan yang transparan, serta menetapkan harga pembelian tandan buah segar tidak sesuai dengan ketentuan pemerintah. Hal ini berimplikasi pada kerugian finansial bagi petani plasma, yang terbebani utang tanpa kejelasan mekanisme pembayaran atas dari kerugian dalam penguasaan sepihak dari pada usaha besar yang memonopili sistem kemitraan. Dalam perspektif istislah, praktik ini bertentangan dengan prinsip keadilan dan kemaslahatan, karena merugikan pihak yang lebih lemah dalam kemitraan.Sebagai saran, diperlukan penguatan regulasi dan pengawasan dari KPPU, termasuk penerapan sanksi yang lebih tegas terhadap pelaku usaha besar yang menyalahgunakan kemitraan. Selain itu, transparansi dalam perjanjian kemitraan harus diperjelas melalui regulasi yang lebih detail, serta pendampingan hukum bagi petani plasma agar mereka memiliki posisi tawar yang lebih kuat dalam perjanjian kemitraan.